Newborn access and care in a health attention program - Poliana Remundini de Lima; Maria Cândida de Carvalho Furtado; Márcia Cristina Guerreiro dos Reis; Débora Falleiros de Mello; Juliana Coelho Pina (Universidade Federal de Goias, 2016)
A cross-sectional study aimed to describe the access and integrality of attention to children before one year old, born between January of 2010 and December of 2012 in a Brazilian city, in a newborn attention program. From the 24.560 children, 55.0% were users of the Unified Health System (SUS); 10.1% children presented low weight at birth; 6,332 (46.9%) children received BCG vaccine at the nursing consultation day; 13,590 (79.5%) children had neonatal screening being less than seven days old; 17,035 (69.4%) children were vaccinated for Hepatitis B at birth. Within SUS users, 68% of children went to nursing consultation at their first week of life and, 37.8% went to a medical consultation being 10 days old. The study presents information of care after birth at the primary healthcare as potential instrument to coordinate assistance to this clientele.